"There's a Whole Different Way of Working with Adolescents": Interviews with Australian Genetic Counselors About their Experiences with Adolescent Clients. Issue 5 (18th May 2013) - Tse, Cheryl; Sahhar, Margaret; Wallace, Jane; Duncan, Rony E.
Abstract: Adolescence is a developmental period marked by unique physical, psychological and social changes. Guidelines about working with adolescents are available to health professionals in other fields, yet few resources are tailored specifically to genetic counselors. The current qualitative study explored the experiences of genetic counselors who work with adolescent clients to determine whether challenges exist and if further training and support are needed. Semi‐structured interviews were conducted with 11 genetic counselors from Australia. Interview transcripts were analyzed using thematic analysis from which 7 key themes emerged: 1) Adolescents: A distinct client group? 2) Characteristics of adolescents; 3) Strategies for working with adolescents; 4) Confidentiality; 5) Parental involvement and presence in sessions; 6) Benefits of working with adolescents; and 7) The effectiveness of past training and education. The findings hold important implications for clinical practice and may inform future training programs and guidelines for genetic counselors internationally.